Dust traffic jams in inclined circumbinary protoplanetary discs – I. Morphology and formation theory. Issue 2 (2nd October 2021) - Aly, Hossam; Gonzalez, Jean-François; Nealon, Rebecca; Longarini, Cristiano; Lodato, Giuseppe; Price, Daniel J
ABSTRACT: Gas and dust in inclined orbits around binaries experience precession induced by the binary gravitational torque. The difference in precession between gas and dust alters the radial drift of weakly coupled dust and leads to density enhancements where the radial drift is minimized. We explore this phenomenon using 3D hydrodynamical simulations to investigate the prominence of these 'dust traffic jams' and the evolution of the resulting dust sub-structures at different disc inclinations and binary eccentricities. We then derive evolution equations for the angular momentum of warped dust discs and implement them in a 1D code and present calculations to further explain these traffic jams. We find that dust traffic jams in inclined circumbinary discs provide significant dust density enhancements that are long lived and can have important consequences for planetesimal formation.